Impact of spray volume and flight speed on the efficiency of drone applications in coffee plants of different ages - Jéssica Elaine Silva; Wender Henrique Batista da Silva; Marcelo Araújo Junqueira Ferraz; Eduardo Augusto Souza Menezes; Octavio Pereira da Costa; Franklin Daniel Inácio; Thiago Orlando Costa Barboza; Christiane Augusta Diniz Melo; Gladyston Rodrigues Carvalho; Adão Felipe dos Santos (Smart Agricultural Technology)
The use of drones in coffee farming has emerged as a solution to optimize phytosanitary and nutritional management, particularly in crops with dense canopies. Effective drone spraying requires precise adjustments to parameters like spray volume and flight speed to maintain application efficiency as the coffee plants grow. This study investigated the efficiency of drone spraying across varying spray volumes and flight speeds in coffee plants of two distinct ages, focusing on droplet deposition within the upper, middle, and lower thirds of the plant canopy. The experiment was conducted in coffee plantations aged 2.5 and 6.5 years, with treatments consisting of four spray volumes (8, 12, 16, and 20 L ha⁻¹) and two flight speeds (12 and 15 km h⁻¹), each replicated three times. Water-sensitive papers were placed in the three canopy layers to assess droplet deposition. In younger coffee plants, the position of the water-sensitive paper showed no significant differences in droplet distribution, while in older plants, larger droplets were predominantly found in the upper third of the canopy. Spray volume and flight speed influenced the droplet spectrum, with volumes of 8 and 16 L ha⁻¹ at 12 km h⁻¹ producing larger droplets in 2.5-year-old plants, whereas 20 L ha⁻¹ at 12 km h⁻¹ resulted in larger droplets in 6.5-year-old plants. These findings underscore the importance of calibrating drone parameters based on plant age, product type, and target location, as spray volume and flight speed significantly affect product distribution and canopy penetration.